Optimalisasi Adsorpsi Kitosan Dari Kitin Cangkang Keong Sawah (Pilla Ampullacea) Terhadap Logam Kadmium (Cd) - Olivia Indra Moray; Djefry Tani; Dokri Gumolung (Jurnal Kimia Fullerene, 2021)
This research aims to make the chitosan from the chitin of the Snail shell (Pilla ampulacea) which can be used as a cadmium metal adsorbent (Cd). It is derived from the isolation of the snail shells through 2 phases, which are deproteination to remove protein and demineralization to remove mineral salts. The formed Kitin is transformed into Chitosan by deacetylated using NaOH 60%. Kitin and Chitosan were acquired, identified by FTIR. The results showed that the chitin yield was 26.81% of the shell weight of 400 grams and the rendemen Chitosan was 31.78% of the weight of chitin. The results of the identification indicate the absorption area of chitin and chitosan function groups, similar to the standard chitin and chitosan uptake areas. Metal adsorption Cd uses adsorbent chitosan from the shell snail (pilla ampulacea) Most optimal occurs at a contact time of 15 minutes and on the weight of adsorbent 0.25 grams, the most optimal absorption occurs at a comparison of 1:30 weight chitosan/volume solution Cd.